Primary investigation on the relationship between microstructural characteristics and the mechanical performance of asphalt mixtures with different compaction degrees. (30th October 2019) - Liu, Pengfei; Hu, Jing; Canon Falla, Gustavo; Wang, Dawei; Leischner, Sabine; Oeser, Markus
Highlights: Relationship between compaction degree and tensile strength is found. Evolution of 3D fractal dimension of air voids is determined. Tensile strength is related to complexity of air void morphology. Abstract: The compaction of asphalt mixtures creates different tensile strengths throughout the asphalt mixture and is thus of importance to ensure durable pavement performance. Asphalt mixtures are composite materials. Therefore, it is necessary to analyse the relationship between the microstructural characteristics and the mechanical performance of asphalt mixtures at different DoCs. In this paper, the 3D microstructures of the asphalt specimens were reconstructed by means of Digital Image Processing (DIP) techniques based on X-ray Computed Tomography (X-ray CT) scanning. Results from the Indirect Tensile Test (ITT) were used to determine the tensile strength of the asphalt specimens. The results show that the relationships between the DoC and the tensile strength as well as the fracture energy are not linear for asphalt specimens at the same testing temperature. This indicates the occurrence of over-compaction during the compaction process. In order to reveal the mechanism of the over compaction at the microscale, the 3D fractal dimension of air voids and aggregates were derived. The 3D fractal dimension of the air voids is variable and constant at first and then becomes smaller during the compaction process. The complexity of the air void morphology is related to the tensile strengths and a hypothesis based on the evolution of 3D fractal dimension of the air voids is proposed in this paper to explain this phenomenon. The results of this research help to increase the understanding regarding the mechanism of over compaction based on the microstructure of the asphalt specimens.